Difficulties and Critical Success Factors for Implementing Industry 4.0 Technologies in the Continuous Process Chemical Industry - Amorim Santos, Paulo Henrique; Zattar, Izabel Cristina; Seleme, Robson (International Journal of Scientific Research and Management (IJSRM), 2021)
Industry 4.0 technologies may provide great improvements in the productive environment of continuous chemical industries. For example, the availability of real-time data management improves unit operations integration in process intensification. This improvements provide increased profitability, safety, sustainability and fault prediction capability. However, the sector presents specific obstacles in deploying 4.0 technologies because of its intrinsic complexity. This paper objective is to identify the sector-specific difficulties and Critical Success Factors when implementing Industry 4.0 technologies. A comprehensive systematic literature review with content analysis was carried out . Among the emerging necessities identified, the need to simplify complex systems and intensify operations is highlighted. The literature also converges on the urgency for developing reliable systems for adverse event management and assessment models for health, safety and environmental management. This paper is therefore both a tool for managers who seek information when implementing 4.0 technologies and researchers who may be looking for new topics in this area. Future research opportunities in the area are also presented.